Multifocal Tubercular Osteomyelitis with Tubercular Breast Abscess: An Atypical Presentation of Tuberculosis - Mita Bar; Tuhin Santra; Pradipta Guha; Neha Agrawal; Apu Adhikary; Anirban Das; Chanchal Mahapatra (Case Reports in Infectious Diseases)
Tuberculosis of spine is common in a developing country like India. However, involvement of spine at multiple levels along with involvement of rib and tubercular breast abscess in an immunocompetent patient without any pulmonary involvement is extremely rare. Here we report a case of 53-year-old immunocompetent lady who presented with quadriparesis and MRI (magnetic resonance imaging) of spine revealed multiple lesions involving cervical, thoracic, lumbar, and sacral region without any involvement of intervertebral disc. On detailed examination she was found to have a lump in right breast. Fine needle aspiration cytology of both paravertebral collection and breast lump revealed presence of acid fast bacilli. She was put on antitubercular drug for one year and she responded well to therapy.